Effective communication as a form of inclusion in the care of hearing-impaired people - Uchôa , Isabela Soares; Santos , Jane Karla de Oliveira; Magalhães , Maria do Amparo Veloso; Freitas , Francisco Ariel Paz Santos; Nascimento , Suzanne Tatianne Teixeira (Seven Editora, 2023)
The objective of this work is to identify, by means of a bibliographical review, the importance of effective communication performed by health professionals as a form of inclusion in the care of hearing-impaired individuals in health services, and the difficulties and obstacles involving this practice. This is a bibliographic research, using the PICo search strategy for the identification and collection of the samples studied, based on the guiding question "What is the importance of effective communication performed by health professionals as a form of inclusion in the care of hearing impaired individuals in health services?". The analysis resulted in 11 articles that were categorized and analyzed according to the profile of the scientific productions and the results in evidence found. The literature showed that health professionals from different specialties, in their great majority, feel unprepared to attend this public, for not knowing how to communicate through the Brazilian Sign Language. This reflects the fragility in the training of these professionals who have no contact with LIBRAS during graduation or after graduation, disrespecting laws that guarantee the right of deaf people. DOI:https://doi.org/10.56238/alookdevelopv1-043